(untitled) (American International Journal of Sciences and Engineering Research, 2021)
Many motors are used for particular reasons in the vicinity, from home appliances to machine tools in manufacturing installations. These motors require comprehensive range features and efficiency, and the speed of the electric motor is often required for most applications. While this is not an issue for motors installed at readily available places, severe problems are presented with powered motors installed in dangerous areas, elevated altitudes, or off-site monitoring of these motors’ speed. The design of a wireless speed control system for these motors is therefore necessary. In addition to ensuring that the wireless speed control of electric motors can readily regulate motors that are moving at high speed, the motor is also easy to use for off-site activities. The precise goal of this study is to create a wireless-based speed control system for an induction motor and to evaluate the finished product. Mechanical loads should not only be driven in industries, but they should also be driven at the desired speed. As a result, techniques for controlling the speed of induction motors are required. After implementing the use of arduino microcontroller and wireless module, we were able to control an induction motor which is an electric fan in this case.